Atmospheric Deposition of Inorganic Elements and Organic Compounds at the Inlets of the Venice Lagoon. (7th July 2014) - Morabito, E.; Contini, D.; Belosi, F.; Stortini, A. M.; Manodori, L.; Gambaro, A.
Abstract : The Venice Lagoon is subjected to long-range transport of contaminants via aerosol from the near Po Valley. Moreover, it is an area with significant local anthropogenic emissions due to the industrial area of Porto Marghera, the urban centres, and the glass factories and with emissions by ships traffic within the Lagoon. Furthermore, since 2005, the Lagoon has also been affected by the construction of the MOSE (Modulo Sperimentale Elettromeccanico—Electromechanical Experimental Module) mobile dams, as a barrier against the high tide. This work presents and discusses the results from chemical analyses of bulk depositions, carried out in different sites of the Venice Lagoon. Fluxes of pollutants were also statistically analysed on PCA with the aim of investigating the spatial variability of depositions and their correlation with precipitations. Fluxes of inorganic pollutants depend differently on precipitations, while organic compounds show a more seasonal trend. The statistical analysis showed that the site in the northern Lagoon has lower and almost homogeneous fluxes of pollutants, while the other sites registered more variable concentrations. The study also provided important information about the annual trend of pollutants and their evolution over a period of about five years, from 2005 to 2010.